CAROLINA HEAVENLY JERUSALEM (VK)
Global Zionism's new colony in North Carolina. They occupy Palestine. They are trying to establish "Heavenly Jerusalem" in Ukraine. They have moved en masse to establish an insular community in Cyprus. They installed Milei in Argentina, and now they are colonizing Patagonia. Now they are invading North Carolina. While they grind down the Amalek through demographic manipulation, war, mass migration, abortion, trans culture, opioid addiction, porno, prostitution ... their long term eugenic program spreads its tentacles around the world. EDIT: added Cyprus